Letter from James Curtis Booth to James B. Guthrie, July 14, 1855 - Booth, James Curtis (1855)
James Curtis Booth (1810-1888), melter and refiner of the United States Mint, writes to James Guthrie (1794-1869), Secretary of the Treasury, to discuss alternatives to the fusible alloy production process patented by Evans.
Keywords: Booth, James Curtis, 1810-1888; Guthrie, James, 1792-1869; United States. Department of the Treasury; United States Mint; Mint of the United States